2021
DOI: 10.1161/jaha.120.019130
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Antiplatelet‐Associated Intracerebral Hemorrhage in the TICH‐2 Randomized Controlled Trial

Abstract: Background Antiplatelet therapy increases the risk of hematoma expansion in intracerebral hemorrhage (ICH) while the effect on functional outcome is uncertain. Methods and Results This is an exploratory analysis of the TICH‐2 (Tranexamic Acid in Intracerebral Hemorrhage‐2) double‐blind, randomized, placebo‐controlled trial, which studied the efficacy of tranexamic acid in patients with spontaneous ICH within 8 hours of onset. Multivariable logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…We agree with many other observational and clinical studies finding increased IHM after HS among those taking OACs, warfarin and non-vitamin K antagonist oral anticoagulants (NOACs) and antiplatelet agents prior to hospitalization [18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We agree with many other observational and clinical studies finding increased IHM after HS among those taking OACs, warfarin and non-vitamin K antagonist oral anticoagulants (NOACs) and antiplatelet agents prior to hospitalization [18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the long-term mortality rate in ICH patients with T2DM is 2.32-fold higher than in those without diabetes [36]. In addition, as expected, and consistent with other investigations, older age, use of OACs and antiplatelet agents, requiring mechanical ventilation, and sepsis were risk factors for IHM in all subgroups [6,8,9,[17][18][19][20][21][22][23]37].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations